ANALYSIS OF DOCUMENTS - Sulaymonov Samariddin; Abdurakhmanova Zilola (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation Analyzing documents helps researchers understand and categorize primary sources or original accounts from people who had personal experiences with the topic. When developing their studies, researchers use established sources to gather ideas and evidence to support their claims. This process allows researchers to evaluate the quality and purpose of the documents they use to determine if the information they contain will benefit their studies. Learning more about this process may help you better organize your resources and perform research more effectively.